2019
DOI: 10.1039/c8ob02996b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the limits of interrupted adenylation domains by engineering a trifunctional enzyme capable of adenylation, N-, and S-methylation

Abstract: The adenylation (A) domains found in nonribosomal peptide synthetases (NRPSs) exhibit tremendous plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…12,23 The results of the substrate proles showed that both Ecm6(AM s M b A) and Ecm6(AM b M s A) were very specic for L-Ser. This along with other engineering studies 12,13 indicate that the natural substrate selectivity is not dramatically altered by insertion of one or two M domains into the a8- it is known that A and T domains can be separated in NRPS systems and investigated independently, 24 some constructs are impaired by improper division of the A and T domains, 25,26 therefore we sought to verify that this was not the case with our engineered interrupted A domain constructs. We found that there was a negligible difference in the relative percent of the adenylation activity with L-Ser between the two enzyme sets (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…12,23 The results of the substrate proles showed that both Ecm6(AM s M b A) and Ecm6(AM b M s A) were very specic for L-Ser. This along with other engineering studies 12,13 indicate that the natural substrate selectivity is not dramatically altered by insertion of one or two M domains into the a8- it is known that A and T domains can be separated in NRPS systems and investigated independently, 24 some constructs are impaired by improper division of the A and T domains, 25,26 therefore we sought to verify that this was not the case with our engineered interrupted A domain constructs. We found that there was a negligible difference in the relative percent of the adenylation activity with L-Ser between the two enzyme sets (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…This is a signicant challenge to overcome for engineering back-to-back interrupted A domains, which was not a problem when only one M domain was articially inserted. 12,13 Until there is a crystal structure solved, we will not know for sure how close together the active sites are for back-to-back interrupted A domains. Alternatively, it could be that the two M domains used in this project were not compatible or did not communicate or coordinate well with each other or the A and T domains, halting methylation.…”
Section: Resultsmentioning
confidence: 99%
“…We could envision that an interrupted A domain of this nature, based on the trends we have observed here, would contain an M s( S ,a2–a3) , as naturally found paired with an M b(a8–a9) interruption. This di-interruption is functionally possible as we showed this conformation can exist artificially, 46 although we have yet to discover a natural di-interrupted A domain like this.…”
Section: Resultsmentioning
confidence: 87%
“…Previous work has shown the malleability of interrupted A domains, in that they can have their M domains exchanged, 47 be created from scratch, 48 and be created to possess unnatural domain arrangements (e.g., a2-a3 and a8-a9 di-interrupted A domains). 46 Most significantly, we have identified two new naturally occurring families of interrupted A domains, containing unique architecture and insertion sites. Family 6 interrupted A domains contain an M domain between a6-a7, a site that was previously unknown to withstand insertions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation